Amish Christmas twins - Gray, Shelley Shepard; Good, Rachel J.; Lough, Loree (Kensington Books, 2020)
"The Christmas not-wish (Shelley Shepard Gray)..."When the foster parents they've cautiously grown to love discover they're expecting, orphaned Roy and Jemima Fisher, ages six and seven, are secretly devastated by the certainty they'll be given up. With Christmas around the corner, their only wish is for new foster parents as nice as Mr. and Mrs. Kurtz. Meanwhile, the Kurtzes have wishes of their own- and with faith, they all may be gifted with twice the blessings . . . "--FantasticFiction.com.